On the Prognostic Power of Tumor-Infiltrating Lymphocytes – A Critical Commentary - Elkoshi, Zeev (Frontiers in Immunology, 2022)
Tumor-infiltrating lymphocytes are extensively used as prognostic biomarkers in cancer. Regulatory T cells (Tregs) or CD8+ T cells in tumor site, or their ratio, are the most common markers used to assess prognosis. This work offers a possible explanation for the opposite correlations between intra-tumoral Tregs and survival, associated with different types of cancer. The complexity involved with the selection of a preferred marker, including the effect of variabilities, is presented and discussed. The lymphocytes ratio is proposed as the marker of choice in most types of cancer. The ratio directly correlate with survival, irrespective of cancer type and is also less variable than each of the two lymphocytes, if their frequencies correlate with each other in the tumor microenvironment. However, if one of the two lymphocytes is highly variable, abandoning the ratio in favor of the less variable lymphocyte will improve correlation with survival, especially when the frequencies of the two species are inversely correlated. It is plausible, that the best prognostic marker will be also be the best predictor of checkpoint inhibitors therapy success.